Assessment of activity moduli and acidic resistance of slag-based geopolymer concrete incorporating pozzolan. (December 2020) - Oyebisi, Solomon; Ede, Anthony; Olutoge, Festus; Olukanni, David
Highlights: The hydraulic activity of GGBFS−CCA blends increases as CaO, MgO, and Al2 O3 increase. Pozzolanic activity of GGBFS−CCA blends increases as SiO2 and Al2 O3 increase. RIs significantly correlate with the flexural strength of GGBFS−CCA GPC. GGBFS−CCA GPC offers a better resistance to acidic attacks. Abstract: The environmental impact of Portland cement production and utilization in the construction sector has led to the global call for the use of eco-friendly construction materials for the production of cleaner and sustainable products. Therefore, this study explored agro-industrial wastes, slag and corncob ash, for the production of geopolymer concrete (GPC). Corncob was dehydroxylated at 600 °C for 3 h and partially used as a replacement for slag at 0%, 20 %, 40 %, 60 %, 80 %, and 100 %. A 12 M, 14 M, and 16 M of both sodium silicate (SS) and sodium hydroxide (SH) were used as activators. The chemical moduli of each and mixed binder were quantified and evaluated based on the major reactive oxides, hence leading to the evaluation of reactivity indexes (RIs). Moreover, the RIs and mix design properties (MDPs) of concrete were used for the prediction of flexural strength while the chemical resistance of each concrete sample was investigated. Compared with the experimental results, the predictive flexural strengths based on the RIs and the MDPs yielded a high precision with R 2 ranging from 88–92 % at 7–90 days, respectively. Moreover, the GPC, unlike Portland cement concrete (PCC), resisted the more acidic attack. Therefore, the use of GGBFS−CCA blended concrete would be more advantageous in a highly acidic environment than PCC. Ultimately, the models proposed by this study can be useful in the concrete mix design procedure for the flexural strength development of GPC incorporating agro-industrial provided the oxide compositions of each and mixed material were obtained.